Mineralogy Constraints on Magmatic Processes Controlling Adakitic Features of Early Permian High-magnesium Diorites in the Western Tianshan Orogenic Belt. (8th January 2021) - He, Peng-Li; Huang, Xiao-Long; Yang, Fan; Wang, Xue
Abstract: Whole-rock geochemistry, usually changed by magmatic processes, might provide misleading information on the petrogenesis of adakites. The Heishantou porphyritic diorites in Nileke, Western Tianshan orogenic belt record complex magma chamber processes, such as magma replenishment, fractional crystallization and crustal contamination, and thus, provide ideal samples for tracing the magmatic processes that generate the typically high Sr and La contents and Sr/Y and La/Yb ratios of adakites. In situ clinopyroxene and amphibole compositions of Heishantou porphyritic diorites (271 ± 2 Ma) are characterized by low Yb and Y content with high Sr/Y and La/Yb ratios, from which calculated early magmas resemble typical adakites derived from partial melting of a subducted slab. But whole-rock composition shows low MgO, Ni and Cr, thus, the Heishantou diorites were previously regarded as the result of partial melting of thickened lower crust. Plagioclase phenocrysts exhibit complex compositional zoning due to magma replenishment, and the rims have higher 87 Sr/ 86 Sr ratio and Sr content than the cores, indicating crustal assimilation. The cores of zoned clinopyroxene phenocrysts have high Mg #, Cr and Ni but low Yb and Y with high Sr/Y and La/Yb ratios, which are consistent with the high Mg # of primary adakitic magmas. Magmatic processes have significantly changed the primary adakitic features of Yb, Y and Sr content, Sr/Y and La/Yb ratios, in addition to Mg # values. The Heishantou primitive high-Mg # adakite was derived from partial melting of a delaminated lower crust followed by storage, recharge, and assimilation in a crustal magma chamber. The Western Tianshan orogenic belt experienced a succession of lower crust delamination events in the Early Permian that involved melting of thickened lower crust, subsequent lithospheric detachment and asthenospheric upwelling.